Case Report: Dilated Cardiomyopathy in a Newborn, a Potential Association With SARS-COV-2 - Azeka, Estela; Arshad, Adam; Martins, Cristiane; Dominguez, Anna Claudia; Siqueira, Adailson; Loss, Andre Silveira; Jatene, Marcelo; Miura, Nana (Frontiers in Pediatrics, 2021)
Abstract: Objective To describe the clinical course of a newborn who developed Dilated Cardiomyopathy (DCM) afterCOVID-19 infection. Methods We retrospectively assessed the clinical notes of a pediatric patient with decompensated heart failure, and who was previously positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Results A 23-day year old newborn presented with diarrhea, hypoactivity, tachypnea and lethargy. The infant progressed to develop respiratory failure and required orotracheal intubation due to apnea. A nasopharyngeal swab tested positive for SARS-COV-2. An echocardiogram demonstrated severe left ventricular dysfunction. The patient was discharged after 18 days with furosemide and angiotensin-converting enzyme inhibitors. During the follow-up period, the infant had two episodes of decompensated heart failure, with evidence of DCM. Investigations for known causes of secondary DCM were negative. The infant was promptly referred for heart transplantation. Conclusion Although rare, we have observed a case of DCM in a newborn following COVID-19 disease. DCM may be a complication following COVID-19 disease in newborns.